Advances in Design by Metallic Materials: Synthesis, Characterization, Simulation and Applications - Fragassa, Cristiano; Epp, Jeremy; Lesiuk, Grzegorz; Zivkovic, Miroslav (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Very recently, a great deal of attention has been paid by researchers and technologists to trying to eliminate metal materials in the design of products and processes in favor of plastics and composites. After a few years, it is possible to state that metal materials are even more present in our lives and this is especially thanks to their ability to evolve. This Special Issue is focused on the recent evolution of metals and alloys with the scope of presenting the state of the art of solutions where metallic materials have become established, without a doubt, as a successful design solution thanks to their unique properties.